Class system to improve the /s/ and /z/ pronunciation through the use of audiovisual resources in english language. - Jara Pando, Ammy Angelica; Eras Zhigue, Scarleth Silvana (Machala: Universidad Técnica de Machala, 2025)
The objective of the research was to enhance the pronunciation of the phonemes /s/ and /z/ in the English language among tenth-grade "A" students in General Basic Education, belonging to an educational institution located in Santa Rosa, El Oro province, during the 2025-2026 school year. This was achieved through the implementation of a class system divided into three structured sessions, which incorporated various audiovisual resources such as YouTube videos, Canva presentations, interactive Wordwall activities, and the Youglish platform as instructional tools. This study followed a quantitative methodological approach, framed within an explanatory experimental design, which allowed the researchers to measure the pedagogical impact of the intervention and verify its influence through the testing of a scientific hypothesis. To ensure comprehensive analysis and data triangulation, both theoretical and empirical level methods were employed for data collection and research validation. The instruments employed included pedagogical tests, such as pre-test and post-test, as well as the application of an observation guide. These tools were aimed at evaluating the initial and final performance of a total of 31 students prior to the implementation of the class system and subsequently at the conclusion of the intervention. The effectiveness of the class system in enhancing pronunciation was verified through the statistical analysis of the test results, using a paired t-test. This analysis provided concrete evidence that the intervention significantly contributed to overcoming students’ difficulties in the articulation and use of the phonemes /s/ and /z/ in English, particularly in terms of intonation, word stress, and fluency.
La investigación se realizó con el fin de mejorar la pronunciación de los fonemas /s/ y /z/ del idioma inglés en los estudiantes de décimo año “A” de Educación General Básica, pertenecientes a una institución educativa ubicada en Santa Rosa, provincia de El Oro, durante el período lectivo 2025-2026, a través de la implementación de un sistema de clases dividida en tres sesiones, y la cual incorporó recursos audiovisuales como videos de YouTube, Canva, Wordwall y Youglish. El estudio se llevó a cabo bajo un enfoque metodológico cuantitativo, con un diseño experimental de carácter explicativo, lo que permitió medir el impacto de la intervención pedagógica y comprobar su influencia a través de la verificación de una hipótesis científica, por medio del empleo de métodos de nivel teórico y empírico para la recolección de datos y sustento de la investigación. Entre los instrumentos utilizados, se aplicaron pruebas pedagógicas como el pre-test y post-test, así como la aplicación de la observación con el fin de evaluar el desempeño inicial de 31 estudiantes antes de implementar el sistema de clases y, posteriormente, al concluir la intervención. La verificación de la efectividad de la aplicación del sistema de clases en la mejora de la pronunciación se llevó a cabo mediante el análisis de los resultados obtenidos de las pruebas aplicadas, utilizando la prueba t pareada. Este análisis estadístico permitió comprobar que la intervención mejoró de manera efectiva las dificultades en el dominio de la pronunciación de los fonemas /s/ y /z/ en el inglés.
Keywords: RECURSOS AUDIOVISUALES; PRONUNCIACIÓN; FONEMAS; PRECISIÓN; FLUIDEZ; ENTONACIÓN Y ACENTUACIÓN